Manajemen Pesantren dalam Pengembangan Kemampuan Membaca Kitab Kuning Santri: Studi Kasus di Pondok Pesantren Tarbiatun Nasyi'in Paculgowang - MUHAMMAD ABDUL FATTAH; ASEP KURNIAWAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the management of Islamic boarding schools (pesantren) in developing students’ ability to read classical Islamic texts (kitab kuning) at Tarbiyatun Nasyi’in Islamic Boarding School, Paculgowang, and to identify the supporting and inhibiting factors affecting the process. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving individuals engaged in the kitab kuning learning process. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that pesantren management is implemented through the integrated functions of planning, organizing, actuating, and controlling. Planning involves the preparation of diniyah learning programs, reinforcement of nahwu and sharaf, and the implementation of sorogan, musyawarah, and takhassus activities. Organizing includes the involvement of kiai, teachers, administrators, and senior students according to their respective responsibilities. Learning implementation applies sorogan, bandongan, musyawarah, lalaran, and memorization methods, while supervision is conducted through regular evaluations and annual examinations. The study shows that the systematic implementation of management functions contributes to students’ ability to read, interpret, understand grammatical rules, and explain the content of classical Islamic texts. Supporting factors include teacher competence, structured learning programs, a conducive learning environment, and senior student involvement. Inhibiting factors consist of differences in students’ initial abilities, limited vocabulary mastery, difficulties in text comprehension, and fluctuating learning motivation. The study concludes that effective and sustainable pesantren management significantly contributes to the development of students’ kitab kuning reading skills.